Rapid Characterization of Microcystin-Producing Cyanobacteria in Freshwater Lakes by TSA-FISH (Tyramid Signal Amplification-Fluorescent In Situ Hybridization) - Brient, Luc; Ben Gamra, Nihel; Periot, Marine; Roumagnac, Marie; Zeller, Perrine; Bormans, Myriam; Méjean, Annick; Ploux, Olivier; Biegala, Isabelle C. (Frontiers in Environmental Science, 2017)
Microcystin (MC) is a common and widespread toxin which represents a health hazard to humans and animals. MC toxin concentrations are monitored by various direct or proxy techniques (HPLC, LC-MS/MS, ELISA, PPIA), however, these techniques do not discriminate producing species from non-producing ones. In order to simultaneously provide the identity and activity of cyanotoxin producing species in freshwater lakes, we applied simple, and fully detailed, whole cell fluorescent in situ hybridization enhanced by tyramid signal amplification (TSA-FISH). DNA oligonucleotide probes MICR3 and MCYA were targeting 16S rRNA and mcyA-mRNA, respectively. The mcyA gene is coding for the MC synthetase enzyme involved in MC synthesis. Controls were acquired with the general eubacterial 16S rRNA probe EUB338, for TSA-FISH assay, and standard HPLC and LC-MS/MS as standard methods for the measurements of MC concentration. Results obtained from monoclonal strains and natural samples demonstrated a specific identification of Microcystis species and were able to discriminate MC producing from non-producing ones. In addition, the MCYA probe allowed the specific detection of MC-synthetase mRNA within Planktothrix isothrix (Oscillatoriale) filaments. Two kinds of mcyA-mRNA labeling were observed in these cells, spots like and plasmid like, which illustrates the well-known plasticity of microbial genome to adapt to environmental stresses. We demonstrated that a simple TSA-FISH assay allows acquiring rapidly dual information of the presence and abundance of potentially toxic species, while identifying species actively producing MC-synthetase mRNA, a proxy of MC toxin. This technique has the potential to be developed into an effective environmental monitoring tool. In addition, detail visualization of cellular mRNAs is powerful for the acquisition of ecological and biomolecular studies of toxic cyanobacteria.